THE MOST DOMINANT LANGUAGE LEARNING STRATEGIES IN LEARNING SPEAKING ENGLISH OF THE MIDWIFERY STUDENTS - Adriani Jihad (Publikasi Pendidikan, 2016)
This research aims: to investigate the most dominant language learning strategies used by successful and unsuccessful students, and to find out the differences of using language learning strategies between successful and unsuccessful students in their speaking.The researcher applied descriptive quantitative method. The population of this research was the fourth semester students of midwifery study program at Universitas Indonesia Timur in academic year 2012/2013. The sample was the fourth semester students of Midwifery Study Program at Universitas Indonesia Timur, class E.11 which consist of 50 students. This research used cluster random sampling technique. This research used 2 kinds of instruments; they were speaking test and questionnaire.The data were collected through speaking tests and SILL questionnaire. The data from speaking test were analyzed by Heaton’s criteria level, whereas the data from questionnaire were analyzed by SPSS 17.00 and Likert scale. The result of the descriptive quantitative data through speaking test showed that (1) the most dominantly used language learning strategies among the successful students is affective strategies and the most frequently used language learning strategies among unsuccessful students choose metacognitive strategy, (2)there is a difference in using language learning strategies between successful students and unsuccessful students. The six language learning strategies usually employed by the students in speaking; the successful students employ all kinds of language learning strategies while the unsuccessful students only employ four kinds of language learning strategies.Keywords:Learning Strategies and English Speaking